Evaluation of acetanilide and antipyrine adsorption on lignin-derived activated carbons. - Gutierrez, Maria del Carmen; García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2024)
In this study, the removal of two emerging pollutants (EPs), antipyrine and acetanilide, through adsorption on activated carbons (ACs) prepared by chemical activation of Organosolv lignin with H3PO4 were evaluated. ACs with different pore size distribution were obtained at different impregnation ratios (H3PO4/lignin, 0.5–3.0 w/w) and activating temperatures (500–900 ◦C). The porosity and surface chemistry of the ACs were determined, and a bimodal size distribution of micropores and narrow mesopores was observed for the different ACs. These ACs were tested for antipyrine and acetanilide adsorption in aqueous solutions in a batch system at 20 ◦C and low concentration levels (0.5–10 ppm). In general, the ACs exhibited higher adsorption affinity to acetanilide than to antipyrine due to its smaller molecular size. Langmuir adsorption isotherm was able to describe the adsorption equilibrium data. A new Linear Driving Force (2-LDF) kinetic model, based on the bimodal size distribution of micropores and narrow mesopores observed for the ACs has been developed. The new model provided a more accurate description of the batch adsorption rates than that obtained from conventional kinetic models, and also enabled to relate the pore size distribution of the adsorbent with the adsorption kinetics. The validity of this model was checked in small-scale column fixed bed adsorption for the AC showing the highest affinity for both EP. The kinetic model and equilibrium adsorption isotherm obtained from the batch experiments were suc- cessfully used to provide an accurate description of the bed service time and the full breakthrough profile of acetanilide and antipyrine.
Keywords: Química; Contaminantes; Acetanilida - Absorción y adsorción; Antipiréticos - Absorción y adsorción; Carbón activado; Lignina; Adsorption; Activated carbons; Lignin; Acetanilide; Antipyrine; Emerging pollutants